Fuzzy Delphi method in education: A mapping - Ciptono, A; Setiyono, S; Nurhidayati, F; Vikaliana, R (Journal of physics. Conference series, 2019)
The Fuzzy Delphi method offers many benefits, including the ability to obtain expert opinion, build consensus, determine the suitability of implementing instructional interventions, forecast trends, and interact with research subjects without being limited by time and space. However, overall understanding of state-of-art in the Fuzzy Delphi Method is still needed. Therefore, this article aims to classify, identify scientific publications, and conduct thematic analyses of the current literature in the Fuzzy Delphi Method to create a broad and detailed understanding, especially in education. The results of this mapping are expected to contribute to researchers and practitioners in determining the gap of the research focus and the next type of research on Fuzzy Delphi Analysis. The research method was carried out by systematic mapping studies (SMS) to study scientific publications Fuzzy Delphi Method in education produced from time to time, the focus of research and the most researched types of paper, and research methods that have been applied. The SMS procedure follows practical guidelines and data mapping using the SCOPUS electronic database library. Based on the results of the SMS on research in the Fuzzy Delphi Method in the field of education it is known that the methods used to determine interactive animation are appropriately applied as learning media, selecting prospective students and determining majors in Vocational High Schools, identifying elements of competencies needed by industry.